2016
DOI: 10.1016/j.ultsonch.2015.05.038
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical model of ice nucleation induced by acoustic cavitation. Part 1: Pressure and temperature profiles around a single bubble

Abstract: This paper deals with the inertial cavitation of a single gas bubble in a liquid submitted to an ultrasonic wave. The aim was to calculate accurately the pressure and temperature at the bubble wall and in the liquid adjacent to the wall just before and just after the collapse. Two different approaches were proposed for modeling the heat transfer between the ambient liquid and the gas: the simplified approach (A) with liquid acting as perfect heat sink, the rigorous approach (B) with liquid acting as a normal h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…It is close to the temperature of the solution rather than that of the core of the bursting bubble. 50 In contrast, the pressure gradient in the vicinity of the bursting bubble is substantially greater than the temperature gradient. 44,[49][50][51][52] Furthermore, for an organic mixture and an aqueous solution, the absolute value of the Soret coefficient is of the order of |S T | ≈ 0.001-0.01 K 1 .…”
Section: Simplified Conservation Of Mass Equationmentioning
confidence: 99%
“…It is close to the temperature of the solution rather than that of the core of the bursting bubble. 50 In contrast, the pressure gradient in the vicinity of the bursting bubble is substantially greater than the temperature gradient. 44,[49][50][51][52] Furthermore, for an organic mixture and an aqueous solution, the absolute value of the Soret coefficient is of the order of |S T | ≈ 0.001-0.01 K 1 .…”
Section: Simplified Conservation Of Mass Equationmentioning
confidence: 99%
“…In the previous paper [4] (part 1), the pressure and temperature fields close to a bubble undergoing inertial acoustic cavitation were simulated and it was shown that extremely strong liquid water pressures but quite moderate temperatures were reached near the bubble wall just after the collapse.…”
Section: Context and Aimmentioning
confidence: 99%
“…The first concern was to determine the undercooling range around the collapsing bubble. The liquid temperature T l profiles near the bubble wall were calculated and shown in part 1 [4] of this paper. The melting temperature T m profiles were obtained from the liquid pressure profiles (see part 1 [4]) using the water solid-liquid equilibrium curve (see Eq.…”
Section: Undercoolingmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences influence the process acceptability, bioavailability, filtration, and tabletting processes of pharmaceutical, food, and specialty materials. Therefore, an effective method for polymorph and pseudo-polymorph control is required in the crystallization process to improve the functionality of crystals and process efficiency [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%